Consumer Protection Against Mismatches Dosages and Highest Retail Prices Minyakita Distribution in Semarang City - Bertha Maulidina; Ubaidillah Kamal (Universitas Negeri Semarang, 2025)
Price fluctuations and the scarcity of cooking oil in Indonesia prompted the government to launch Minyakita as a subsidy product with the Highest Retail Price (HET) setting. However, the implementation of Minyakita distribution in Semarang City still raises various problems, especially related to mismatches in doses and violations of the HET. This research aims to examine legal provisions, the implementation of supervision, and the form of legal protection for consumers for these violations. This study uses an empirical juridical approach with a qualitative type. The results of the study showed that there was a practice of filling the dosage that did not match the packaging label and the selling price was above the HET (Rp15,700 per liter) which was Rp16,000-Rp17,000 per liter, which was clearly detrimental to consumers. On the other hand, supervision by the Trade Office and the Legal Metrology Unit has not run optimally due to limited resources and low public awareness in using the complaint mechanism. In conclusion, although there is a strong legal basis such as Law No. 8 of 1999, BPOM Regulation No. 31 of 2018, and Permendag No. 18 of 2024, the implementation of consumer protection is still weak at the regional level. Therefore, it is recommended to strengthen decentralized supervision, increase consumer education, and apply strict sanctions to violating business actors, in order to realize a fair, transparent, and community-friendly cooking oil distribution system.